Tensor Algebras of Bimodules and Their Representations - Gubareni, Nadiya (Sarajevo Journal of Mathematics, 2024)
We study $(D,{\cal O})$-species, which are a special case of species introduced by Yu. A. Drozd (1980). The representations of $(D,{\cal O})$-species and modules over the corresponding tensor algebras of bimodules are considered. We find necessary and sufficient conditions on a special kind of $(D,{\cal O})$-species under which they are of bounded representation type. The conditions are given in terms of Dynkin diagrams and diagrams with weights. The connection of these $(D,{\cal O})$-species and corresponding tensor algebras with right hereditary semiperfect and semidistributive rings are studied. * This paper was presented at the International Scientific Conference Graded structures in algebra and their applications, dedicated to the memory of Prof. Marc Krasner, IUCDubrovnik, Croatia, September, 22-24, 2016.